PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS SEARCH, SOLVE, CREATE, AND SHARE PADA PRAKTIKUM MANDIRI MATERI MOLLUSCA DAN ARTHROPODA - Rahmatika, Fitrianingsih; Alimah, Siti (Journal of Biology Education, 2014)
Abstract ___________________________________________________________________The aims of this research are to develop student worksheet based on Search, Solve, Create, and Share model and to measure the effectiveness of student worksheet for the student learning achievement, thinking skills, activities, and scientific attitude of Molluscs and Arthropods concept. Based on initial observation, known that needs to develop LKS which has never been used in the learning of Molluscs and Arthropods. This is an R&D research with pretest-posttest comparison group design. Large-scale field-testing in this research was class X.IPA.1, X.IPA.3, dan X.IPA.7 in Senior High School 1 of Tegal. Result of student worksheet development in terms of its material feasibility aspect was 75,75% and media feasibility 83,9%. Normalized gain score was 0,62, indicating that there was an increasing learning achievement from pretest to posttest under medium category. The average classical completeness of students reached 82,96%. The average percentage classical of students for the thinking skills, activities, and scientific attitude of student are 77,7%; 77,04%, and 77,76%. It was concluded that student worksheet on the basis of Search, Solve, Create, and Share model was feasible and effectively applied for learning of Molluscs and Arthropods concept.  Abstrak___________________________________________________________________Penelitian ini bertujuan untuk mengembangkan LKS berbasis Search, Solve, Create, and Share dan mengukur keefektivan LKS terhadap hasil belajar, keterampilan berpikir, aktivitas, sikap ilmiah dalam pembelajaran Mollusca dan Arthropoda. Berdasarkan observasi awal diketahui bahwa perlu dikembangkan LKS yang belum pernah digunakan dalam pembelajaran Mollusca dan Arthropoda. Penelitian menggunakan metode penelitian Research and Development dengan desain pretest-posttest comparison group. Uji skala besar dalam penelitian adalah siswa kelas X.IPA.1, X.IPA.3, dan X.IPA.7 di SMA Negeri 1 Tegal. Hasil pengembangan LKS, aspek kelayakan materi memperoleh skor 75,75% dan kelayakan media 83,9%. Nilai gain ternormalisasi sebesar 0,62 menunjukkan adanya peningkatan hasil belajar dari pretest ke posttest dengan kategori sedang. Rata-rata ketuntasan klasikal siswa mencapai 82,96%. Rata-rata persentase klasikal keterampilan berpikir; aktivitas; dan sikap ilmiah siswa berturut-turut yaitu 77,7%; 77,04%, dan 77,76%. Berdasarkan hal tersebut disimpulkan bahwa LKS berbasis Search, Solve, Create, and Share layak dan efektif diterapkan dalam pembelajaran Mollusca dan Arthropoda.